Model calculations of the contribution of tropospheric SO2 to the stratospheric aerosol layer - Nalapalu, Chiranjeevi Srinivasan (Dr.) (2025)
The stratospheric aerosol layer is an important part of the Earth’s atmosphere. It plays a significant role in the radiative balance of the Earth, in stratospheric chemistry and in geo-engineering. Changes in composition in the aerosol layer after volcanic eruptions have been shown to cause an average global cooling effect. Polar stratospheric clouds formed from sulfate aerosols initiate anthropogenic ozone depletion in the Antarctic region. Sulfate aerosols have also been considered in Stratospheric Aerosols Injection experiments in the aerosol layer to reduce global warming. As one can see, the changes in the composition of this layer can have adverse effects on the Earth’s climate. Various aspects of the stratospheric aerosol layer have been studied but many processes in the aerosol layer are still not fully understood. In this study we specifically focus on the the contribution of tropospheric sulfur dioxide SO2 to the stratospheric aerosol layer. Sulfur aerosols in the aerosol layer originate from sulfur containing gases in the troposphere. The sulfur containing gases are transported from the troposphere to the stratosphere through a combination of cross isentropic transport of air and direct injection of air in overshooting convection events. Volcanic eruptions, which are rare, directly transport massive amounts of sulfur containing gases from the Earth’s interior to the aerosol layer. However, there have been been few studies focused on the transport of tropospheric SO2 in volcanically quiescent periods. Even fewer model studies simulate convection in their model. We attempt to model this process in our study and use convection as one of the parameters in our model. SO2 and OCS are the two main contributors of sulfur to the aerosol layer. In this study we specifically choose to study SO2. To explore our research question we simulate the transport and chemistry of SO2 in the troposphere by running a chemical box model on a high number of trajectories ascending from the boundary layer to the tropopause. The ...